Research on HTLV-1 and HTLV-2 in Latin America and the Caribbean over the last ten years - Solorzano-Salazar, Dustin M. (2023)
Worldwide, Human T-lymphtropic virus-1 and 2 (HTLV-1 and 2) infects approximately more than 10 million people, mostly occurring in hyperendemic areas such as the region of Latin America and the Caribbean (LAC). A comprehensive bibliographic exploration of original articles published on the Web of Science Core Collection database over the last 10 years was done. A bibliometric analysis was performed using the bibliometrix package in RStudio and VOSviewer. A total of 519 articles published in 194 journals were identified along the 10 years studied. In 2012 the peak number of publications was identified and the average number of citations per document was 1.33. Galvao-Castro B was the author with the greatest number of publications. Aids Research and Human Retroviruses was the most productive journal, and the study by Bangham CRM was the most cited. Brazil was the country with most corresponding authors that had the most publications and the most significant number of total citations. Infections and HTLV-1 were the most used keywords. In conclusion, according to the current quantitative analysis, there is a need for more significant promotion of research on HTLV-1 and 2 among the scientific community of LAC.